Development and external validation of a biopsy‐derived nomogram to predict risk of ipsilateral extraprostatic extension. (6th January 2017) - Sayyid, Rashid; Perlis, Nathan; Ahmad, Ardalanejaz; Evans, Andrew; Toi, Ants; Horrigan, Michael; Finelli, Antonio; Zlotta, Alexandre; Kulkarni, Girish; Hamilton, Robert; Morash, Christopher; Fleshner, Neil
Abstract : Objectives: To develop and externally validate a nomogram that predicts risk of side‐specific extraprostatic extension (EPE) at time of surgery, using commonly available preoperative markers. Materials and Methods: A consecutive sample of 753 men treated by radical prostatectomy (RP) at the University Health Network, Toronto, between 2009 and 2015, was used to develop the nomogram. The validation cohort consisted of 311 men treated by RP at Ottawa Hospital Research Institute, between 1992 and 2014. The study outcome was presence of ipsilateral EPE. The association between predictors considered and EPE was tested using univariate and multivariate logistic regression analyses. The predictive accuracy of the nomogram was determined using the area under the receiver‐operating characteristic curve. Results: The overall rate of EPE was 19.8% of all lobes in the developmental cohort and 28.9% in the validation cohort. Significant variables in the models were age, prostate‐specific antigen and ipsilateral Gleason score, percentage of positive cores and highest core involvement (all P < 0.05). The nomogram predicting risk of EPE had a predictive accuracy of 0.74 in the external validation cohort. Conclusion: We developed and externally validated a nomogram that predicts the risk of ipsilateral EPE based on commonly used preoperative markers. This nomogram may be used to assist surgical decision‐making prior to RP.